Rusty Microglia: Trainers of Innate Immunity in Alzheimer's Disease - Sfera, Adonis; Gradini, Roberto; Cummings, Michael; Diaz, Eddie; Price, Amy I.; Osorio, Carolina (Frontiers in Neurology, 2018)
Highlights -LPS activates microglial TLRs, training these cells excessively and triggering the release of C1q, TNF-alpha and IL-1 alpha, biomolecules associated with autoimmunity. -A1 astrocytes, likely autoimmune, eliminate viable neurons and oligodendrocytes, contributing to Alzheimer’s disease neuronal and synaptic loss. -LPS, a danger signal, promotes intracellular iron sequestration, increasing the risk of ROS. LPS also promotes ferritinophagy, increasing the free intracellular iron levels. -ROS and iron activate NLRP3 inflammasomes, generating prolonged inflammation which may override microglial tolerization, engendering autoimmune A1 astrocytes. -Promoting tolerization and lowering training may de-escalate microglia, lowering the risk of neuronal loss and Alzheimer’s disease. Alzheimer’s disease, the most common form of dementia, is marked by progressive cognitive and functional impairment believed to reflect synaptic and neuronal loss. Recent preclinical data suggests that lipopolysaccharide (LPS)-activated microglia may contribute to the elimination of viable neurons and synapses by promoting a neurotoxic astrocytic phenotype, defined as A1. The innate immune cells, including microglia and astrocytes, can either facilitate or inhibit neuroinflammation in response to peripherally applied inflammatory stimuli, such as LPS. Depending on previous antigen encounters, these cells can assume activated (trained) or silenced (tolerized) phenotypes, augmenting or lowering inflammation. Iron, reactive oxygen species (ROS) and LPS, are microglial activators, but only the latter can trigger immune tolerization. In Alzheimer’s disease, tolerization may be impaired as elevated LPS levels, reported in this condition, fail to lower neuroinflammation. Iron is closely linked to immunity as it plays a key role in immune cells proliferation and maturation, but it is also indispensable to pathogens and malignancies which compete for its capture. Danger signals, including LPS, induce intracellular iron sequestration in innate immune cells to withhold it from pathogens. However, excess cytosolic iron increases the risk of inflammasomes’ activation, microglial training and neuroinflammation. Moreover, it was suggested that free iron can awaken the dormant central nervous system (CNS) LPS-shedding microbes, engendering prolonged neuroinflammation that may override immune tolerization, triggering autoimmunity. In this review, we focus on iron-related innate immune pathology in Alzheimer’s disease and discuss potential immunotherapeutic agents for microglial de-escalation along with possible delivery vehicles for these compounds.